2013
DOI: 10.1371/journal.pone.0053362
|View full text |Cite
|
Sign up to set email alerts
|

Different Environmental Drivers of Highly Pathogenic Avian Influenza H5N1 Outbreaks in Poultry and Wild Birds

Abstract: A large number of highly pathogenic avian influenza (HPAI) H5N1 outbreaks in poultry and wild birds have been reported in Europe since 2005. Distinct spatial patterns in poultry and wild birds suggest that different environmental drivers and potentially different spread mechanisms are operating. However, previous studies found no difference between these two outbreak types when only the effect of physical environmental factors was analysed. The influence of physical and anthropogenic environmental variables an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 16 publications
2
104
1
2
Order By: Relevance
“…The presence of avian influenza in wild water birds and the frequency of direct or indirect contact between reservoir birds and poultry are risk components that enable transmission from wild birds to poultry. However, in addition to the higher introduction rate on outdoor-layer farms (this study) and the genetic relationship of wild bird strains and avian influenza outbreak viruses ( 17 ), no scientific data have been available that could support this assumption, although physical environmental factors, such as surface water availability and proximity to lakes and wetlands, have been suggested as drivers of HPAIV H5N1 outbreaks in poultry and wild birds ( 18 , 19 ). …”
Section: Discussionmentioning
confidence: 95%
“…The presence of avian influenza in wild water birds and the frequency of direct or indirect contact between reservoir birds and poultry are risk components that enable transmission from wild birds to poultry. However, in addition to the higher introduction rate on outdoor-layer farms (this study) and the genetic relationship of wild bird strains and avian influenza outbreak viruses ( 17 ), no scientific data have been available that could support this assumption, although physical environmental factors, such as surface water availability and proximity to lakes and wetlands, have been suggested as drivers of HPAIV H5N1 outbreaks in poultry and wild birds ( 18 , 19 ). …”
Section: Discussionmentioning
confidence: 95%
“…In addition, H7 viruses with multiple NA subtypes were found in ducks in Jiangxi province (in South Central), suggesting an epidemiological bridge from migratory birds to sentinel farm ducks and then to market birds. Epidemiological studies also suggested that HPAI H5N1 outbreaks in poultry mostly occurred in areas which overlapped with habitats for wild birds, whereas outbreaks in wild birds were mainly found in areas where food and shelter are available [48]. Bidirectional movement of wild birds among the provinces along the flyway route in south central areas were identified in studies tracking the movements of migrating wild birds, and the transmission of HPAI H5N1 to Qinghai lake (Northwest) have also been identified [15, 49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…Infections with avian influenza virus (AIV) strains have become highly prevalent in poultry worldwide [14]. Avian influenza (AI) is a leading cause of morbidity, mortality, and economic loss in many countries.…”
Section: Introductionmentioning
confidence: 99%